The successful synthesis of industrial isomaltooligosaccharides lies in the use of transglycosylating α-glucosidases: A review - Sandeep Kumar; Trisha Tissopi; Sarma Mutturi (Carbohydrate Polymer Technologies and Applications, 2023)
Consumption of oligosaccharides which can evade host digestive enzymes but can be selectively taken-up by populations of bacteria native to the host colon in situ, improves the gut health of host through various mechanisms. However, their consumption from natural sources is constrained by adequacy, bioavailability and geography. Here in the present review, we detail the enzymatic production and applications of promising multifunctional dietary molecule “isomaltooligosaccharides (IMO)”. Although presently IMO are not considered as dietary fibers (vide FDA-2019-P-2239), these are proven as slowly digestible carbohydrates with multiple food applications and health benefits. Commercially IMO are synthesized using transglycosylating α-glucosidase (tAG) with pretreated starch as the substrate. Usually, the tAG obtained from Aspergillus spp. are widely used to produce IMO. The present review provides comprehensive information on tAG from different sources and their applications. Strategies to increase the transglycosylation to hydrolysis ratio by tAG is of both scientific and commercial interest. Some of the existing strategies to improve this ratio are detailed in this review. This review describes the use and application of IMO in food industry and its potential as functional oligosaccharides. Apart from production strategies, both food applications of IMO and their health benefits are discussed.